Plankton lifeforms as a biodiversity indicator for regional-scale assessment of pelagic habitats for policy. (June 2019) - McQuatters-Gollop, Abigail; Atkinson, Angus; Aubert, Anaïs; Bedford, Jacob; Best, Mike; Bresnan, Eileen; Cook, Kathryn; Devlin, Michelle; Gowen, Richard; Johns, David G.; Machairopoulou, Margarita; McKinney, April; et al.
Graphical abstract: Highlights: Plankton are sensitive indicators of ecosystem change. Marine Strategy Framework Directive requires Good Environmental Status for UK seas. A plankton lifeforms indicator is policy-approved to assess pelagic biodiversity. This indicator displayed spatially-variable changes in plankton in the past decade. This is the first assessment of the pelagic plankton community on a UK-wide scale. Abstract: Plankton are sensitive indicators of change and, at the base of marine food webs, they underpin important ecosystem services such as carbon sequestration and fisheries production. In the UK and the Northeast Atlantic region, change in plankton functional groups, or 'lifeforms', constructed based on biological traits, is the formally accepted policy indicator used to assess Good Environmental Status (GES) for pelagic habitats under the Marine Strategy Framework Directive (MSFD: 2008/56/EC). To identify changes in UK pelagic habitats, plankton lifeforms, were used from diverse UK data sets collected by different methods, including plankton sampling by nets, water bottles, integrating tube samplers, and the Continuous Plankton Recorder. A Plankton Index approach was used to identify change in plankton lifeforms. This is the first time that the pelagic plankton community has been assessed on a UK-wide scale and forms the foundation of the UK's 2020 MSFD Assessment for pelagic habitat biodiversity and food webs. This approach revealed that some of the plankton lifeforms used in the assessment displayed spatially-variable changes during the past decade. Assessing plankton community change using a common indicator at the UK scale for the first time is a significant step towards evaluating GES for European seas. Determining GES for pelagic habitats, however, is a challenging process, with additional work required to interpret the assessment results and to identify causation of the changes observed.